Analisis Ketahanan Usaha Pengolahan Petis Ikan Sebelum dan Selama Masa Pandemi Covid-19 di Desa Prenduan Kecamatan Pragaan Kabupaten Sumenep - Amilia Silfa Istiqhfariyah; Hapsari Wiji Utami (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2021)
This study aims to determine the condition of the fish petis processing business before and during the covid-19 pandemic, and to find out the efforts made by fish petis entrepreneurs in surviving the covid-19 pandemic. One way to empathize and maintain communication with customers, with current conditions it is very important to maintain health, can actively inform that this fish petis business is implementing according to government regulations by preventing virus transmission such as spraying disinfectants, checking the body temperature of workers. This is done in order to maintain consumer confidence that this fish paste business can be marketed as before